Оптимізація інтенсивної терапії в періопераційному періоді багатоетапної оперативної корекції з періодами очікування при політравмі - Матвєєнко, М.С.; Matvieienko, M.S. (Харків : Харківський національний університет імені В.Н. Каразіна, 2020)
Matvieienko M.S. Optimization of intensive care in the perioperative period of multistage surgery correction with waiting periods at polytrauma. – Qualification scholarly paper: a manuscript. Thesis submitted for obtaining the Doctor of Philosophy degree in specialty 222 – Medicine (22 – Health Care). – V.N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, 2020. The study is devoted to investigation of the effects, justification of the metabolic drugs administrution as a component of intensive care in the perioperative period of multistage surgery correction with waiting periods at polytrauma. The special significance of acute massive blood loss in the pathogenesis of traumatic disease is currently considered indisputable. That is why eliminating the deficit of circulating blood volume is a priority of intensive care. Hypoxia, hypoperfusion, ischemia quickly lead to the activation of protective and adaptive reactions and subsequently to secondary tissue damage. There is very limited information about the development, the severity of adaptive reactions in severe combined trauma on the background of operative stress when it is necessary to conduct a series of staged surgical interventions. The level of mortality and complications in multiple trauma remains very high throughout the world. In this regard, it seems important to study and implement new treatment algorithms using effective metabolic means of pharmacological correction.
Optimization of intensive care in the perioperative period of multistage surgery correction with waiting periods at polytrauma
Дослідження присвячене вивченню ефектів, обґрунтуванню впровадження препаратів метаболічної дії в якості компоненту інтенсивної терапії в періопераційному періоді багатоетапної оперативної корекції з періодами очікування при політравмі. Особлива значимість гострої масивної крововтрати в патогенезі травматичної хвороби на даний час вважається беззаперечною. Саме тому усунення дефіциту об’єму циркулюючої крові є пріоритетним напрямком інтенсивної терапії. Гіпоксія, гіпоперфузія, ішемія швидко призводять до активації захисно-пристосувальних реакцій і в подальшому до вторинного пошкодження тканин. Досить обмеженими є відомості про розвиток, ступінь вираженості адаптивних реакцій при тяжкій поєднаній травмі на тлі операційного стресу при необхідності проведення серії етапних оперативних втручань. При цьому рівень смертності й ускладнень при політравмі залишається дуже високим в усьому світі. У зв’язку з чим видається актуальним дослідження й впровадження нових алгоритмів лікування з використанням ефективних метаболічних засобів фармакологічної корекції.
Keywords: Research Subject Categories::MEDICINE; політравма; інтенсивна терапія; шок; багатоетапна оперативна корекція; гемодинаміка; гіпоксія; операційний стрес; D-фруктозо-1,6-дифосфат натрієвої солі гідрат; ускладнення; polytrauma; intensive care; shock; multi-stage surgical correction; hemodynamic; hypoxia; surgical stress; D-fructose-1,6-diphosphate sodium salt hydrate; complications